UPAYA GURU EKSTRAKURIKULER TAHFIDZ DALAM MENINGKATKAN TAJWID DENGAN PENDEKATAN TAHFIDZ SISWA DI MTS MUHAMMADIYAH 1 KOTA PROBOLINGGO - Nur Masfufatul Izzah; Badiatul Munawaroh; Sufiya; Muhammad Rizal; Sorleeheen Doima; Devy Habibi Muhammad (As-Sulthan Journal of Education, 2026)
This study aims to describe the learning process of the tahfidz extracurricular program and to identify the difficulties experienced by students in memorizing the Qur'an and applying the rules of tajwid at MTs Muhammadiyah 1 Probolinggo City. This research employed a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation involving the tahfidz extracurricular teacher and students. The findings indicate that the learning process was carried out through several stages, namely muraja'ah (review), talqin, talaqqi, drilling, and direct correction of recitation errors. These strategies were effective in improving students' Qur'anic reading skills, particularly in the pronunciation of makhraj (articulation points of letters) and the application of tajwid rules. The students' difficulties included the influence of the local dialect on the pronunciation of Arabic letters, errors in applying vowel length, lack of muraja'ah practice at home, low learning motivation and concentration, and differences in students' Qur'anic reading abilities. To address these challenges, the teacher set memorization targets according to students' abilities, increased reading practice before introducing new memorization, provided individual guidance, and involved parents in supervising muraja'ah activities at home. These strategies gradually improved the students' Qur'anic reading and memorization abilities, although continuous guidance remains necessary.